2018
DOI: 10.1371/journal.pntd.0006140
|View full text |Cite
|
Sign up to set email alerts
|

Accomplishing the genotype-specific serodiagnosis of single and dual Trypanosoma cruzi infections by flow cytometry Chagas-Flow ATE-IgG2a

Abstract: The methods currently available for genotype-specific diagnosis of T. cruzi infection still present relevant limitations, especially to identify mixed infection. In the present investigation, we have evaluated the performance of Chagas-Flow ATE-IgG2a test for early and late differential diagnosis of single and dual genotype-specific T. cruzi infections. Serum samples from Swiss mice at early and late stages of T. cruzi infection were assayed in parallel batches for genotype-specific diagnosis of single (TcI, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…This phenomenon may reflects the phylogenetic origin of T. cruzi DTUs 5 indicating TcI and TcII as ancestors DTUs with polarized biological features 8,9,[60][61][62][63][64] and TcVI as a hybrid DTU presenting intermediate profile 8,60,61 . Corroborating the previous findings from Alessio et al 30 for experimental T. cruzi infection, the present work also identified TcI antigen as the root attribute in the decision tree algorithms proposed for DTUspecific diagnosis of human infection.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This phenomenon may reflects the phylogenetic origin of T. cruzi DTUs 5 indicating TcI and TcII as ancestors DTUs with polarized biological features 8,9,[60][61][62][63][64] and TcVI as a hybrid DTU presenting intermediate profile 8,60,61 . Corroborating the previous findings from Alessio et al 30 for experimental T. cruzi infection, the present work also identified TcI antigen as the root attribute in the decision tree algorithms proposed for DTUspecific diagnosis of human infection.…”
Section: Discussionsupporting
confidence: 85%
“…Battacharyya et al 27 demonstrated that TSSA lineage serology lacks specificity to detect TcI DTU. More recently, the Chagas-Flow ATE-IgG2a has been presented as an innovative method with outstanding performance for universal and DTU-specific diagnosis of experimental T. cruzi infection 29,30 . Moreover, the Human Chagas-Flow ATE-IgG1 methodology has been developed and standardized showing elevated performance for universal diagnosis and post-therapeutic cure assessment in Chagas disease 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed infections, such as TcI and TcII, may occur in single mammals, and are not currently detectable by lineage-specific serology; nevertheless, due to sustained infection antibodies to TcII should not be lost. The Chagas Sero K-SeT RDT described here does not make redundant T. cruzi genotyping, or advanced analytical techniques such as flow cytometry [47]; however, by detecting lineage-specific host IgG, it can provide epidemiological information when direct parasite genotyping is hampered or subject to confounding biases.…”
Section: Discussionmentioning
confidence: 99%